Endothelial cell Piezo1 promotes vascular smooth muscle cell differentiation on large arteries - Javier Abello; Ying Yin; Yonghui Zhao; Josh Maurer; Jihui Lee; Cherokee Bodell; Jahmiera Richee; Abigail J. Clevenger; Zarek Burton; Megan E. Goeckel; Michelle Lin; Stephanie Grainger; et al. (European Journal of Cell Biology)
Vascular stabilization is a mechanosensitive process, in part driven by blood flow. Here, we demonstrate the involvement of the mechanosensitive ion channel, Piezo1, in promoting arterial accumulation of vascular smooth muscle cells (vSMCs) during zebrafish development. Using a series of small molecule antagonists or agonists to temporally regulate Piezo1 activity, we identified a role for the Piezo1 channel in regulating klf2a, a blood flow responsive transcription factor, expression levels and altered targeting of vSMCs between arteries and veins. Increasing Piezo1 activity suppressed klf2a and increased vSMC association with the cardinal vein, while inhibition of Piezo1 activity increased klf2a levels and decreased vSMC association with arteries. We supported the small molecule findings with in vivo genetic suppression of piezo1 and 2 in zebrafish, resulting in loss of transgelin+ vSMCs on the dorsal aorta. Further, endothelial cell (EC)-specific Piezo1 knockout in mice was sufficient to decrease vSMC accumulation along the descending dorsal aorta during development, thus phenocopying our zebrafish data, and supporting functional conservation of Piezo1 in mammals. To determine the underlying mechanism, we used in vitro modeling assays to demonstrate that differential sensing of pulsatile versus laminar flow forces across endothelial cells changes the expression of mural cell differentiation genes. Together, our findings suggest a crucial role for EC Piezo1 in sensing force within large arteries to mediate mural cell differentiation and stabilization of the arterial vasculature.